Konversi Hutan Menjadi Tanaman Kayu Manis dan Kopi terhadap Kemantapan Agregat Andisol di Kecamatan Lembah Masurai Kabupaten Merangin - Nasution, Hasriati; Suryanto, Suryanto; Saad, Asmadi (CV. Creative Tugu Pena, 2024)
Andisol is soil located in volcanic mountain areas with the characteristics of black or dark soil and is formed from volcanic ash. The main problem is that Andisol soil has andic properties if the soil is dry, the soil does not easily absorb water anymore and the aggregate stability is low so it is easy for soil particles to be eroded from the hill. andosol. The aim of the research was to examine the influence of cinnamon and coffee plants on the stability of Andisol aggregates, relatively similar to forest soil. The usefulness of research on cinnamon and coffee plants is expected to be able to replace forest vegetation in the physical properties of Andisol soil. The research was carried out in Lembah Masurai District, Merangin Regency. at an altitude of 1300 m above sea level with the Andisol type. The research was carried out over 4 months in 2024. Soil analysis was carried out at the Soil Physics and Chemistry Laboratory, Faculty of Agriculture, Jambi University. Soil sampling to determine soil aggregate density, organic matter content, bulk volume and soil permeability was carried out by survey using the Proportive Random Sampling method in areas planted with cinnamon, coffee, cinnamon mixed with coffee plants and forest soil on a slope of 8% - 15 %. The parameters observed were organic matter content, permeability, soil volume weight, total pore space, aggregate percentage, soil aggregate stability. Each treatment was repeated 15 times. To differentiate the physical properties of Andisol, cinnamon, coffee, cinnamon mixed with coffee and forest soil were planted. carried out with the Unpaired Middle Value Test at the 5% level (Steel and Torrie, 1995). From the results of the Unpaired Middle Value Test, it was found that replacing forest with cinnamon plants, the organic matter content, aggregate percentage, and aggregate stability were the same as forest soil but different from coffee plantings and mixed cinnamon and coffee plantations. Keywords: Forest Conversion to Cinnamon, Stability of Andisol, Andisol